Pengaruh Harga Terhadap Keputusan Pembelian Lapis Talas Kujang Bogor untuk Keperluan Usaha Waralaba - Mohammad Noorman Mulyadi (Jurnal Ilmiah Manajemen Kesatuan, 2022)
The purpose of this study was to determine the effect of price on purchasing decisions of taro layer cake of Kujang Bogor for franchise business purposes. The method used in this study is a quantitative method. The population in this study were consumers who had purchased an unlimited number of taro layer cakes of Kujang Bogor and the sample to be used in this study was 100 respondents. The analytical tool used is simple linear regression with the help of the SPSS 25 application program. The results obtained are that the price has a negative effect on purchasing decisions for the taro layer of Kujang Bogor for franchise business purposes. The amount of influence caused by the price is 0.514 or 51.4%, which means that the price variable is able to influence the purchasing decision variable by 51.4%. While the remaining 48.6% is influenced by other factors outside the variables studied, such as product quality, service quality, brand image, etc. Keywords: Price, purchasing decisions, taro layer cake of kujang Bogor